2021
DOI: 10.3389/fonc.2021.718532
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAPLINC Promotes Renal Cell Cancer Tumorigenesis by Targeting the miR-135b-5p/CSF1 Axis

Abstract: BackgroundLong noncoding RNAs (lncRNAs) are closely related to the occurrence and development of cancer. Gastric adenocarcinoma-associated, positive CD44 regulator, long intergenic noncoding RNA (GAPLINC) is a recently identified lncRNA that can actively participate in the tumorigenesis of various cancers. Here, we investigated the functional roles and mechanism of GAPLINC in renal cell carcinoma (RCC) development.MethodsDifferentially expressed lncRNAs between RCC tissues and normal kidney tissues were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…CSF1 acts as a tumour-promoting cytokine by recruiting macrophages to the tumour area, which in turn leads to the release of various tumour-promoting growth factors in the microenvironment (32). In vitro and in vivo studies have confirmed that CSF1 promotes proliferation and reduces apoptosis in renal cell carcinoma (33). TUBB2B alterations can lead to increased incidence of kidney disease and KIRC (34).…”
Section: Discussionmentioning
confidence: 99%
“…CSF1 acts as a tumour-promoting cytokine by recruiting macrophages to the tumour area, which in turn leads to the release of various tumour-promoting growth factors in the microenvironment (32). In vitro and in vivo studies have confirmed that CSF1 promotes proliferation and reduces apoptosis in renal cell carcinoma (33). TUBB2B alterations can lead to increased incidence of kidney disease and KIRC (34).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LINC00460 in head and neck squamous cell carcinoma facilitates peroxiredoxin-1 entry into the nucleus, thereby promoting cell proliferation and metastasis ( Jiang et al, 2019 ). Knockdown of lncRNA GAPLINC repressed the tumor growth in renal cell cancer, while overexpression of GAPLINC facilitated tumorigenesis via the miR-135b-5p/CSF1 axis, indicating poor survival ( Wang et al, 2021c ). On the other hand, Yang and colleagues revealed that lncRNA MYOSLID played a critical role in the progression of osteosarcoma through the miR-1286/RAB13 axis ( Yang et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hours of incubation, the cells in the lower chamber were collected, fixed and stained. Other cell function assays, such as plate colony formation [11] and Cell Counting Kit-8 (CCK-8) assays [12] and flow cytometry analyses of the cell cycle [13] and apoptosis [14] , were conducted as previously described.…”
Section: Methodsmentioning
confidence: 99%